Community Empowerment Through the Village Savings and Lending Associations (VSLA) Programme in Guruve, Zimbabwe - Savadye, Lilian Tariro; Mwapaura, Kudzai (Jurnal Karya Abdi Masyarakat, 2025)
Limited access to financial services, low levels of financial literacy, and insufficient business mentoring remain major challenges for rural communities in Guruve, Zimbabwe, weakening household economic resilience. To address these issues, this community service activity aimed to describe the implementation of the Village Savings and Lending Associations (VSLA) programme initiated by the Salvation Army and its contribution to community economic empowerment. The activity was conducted using a participatory approach through focus group discussions, key informant interviews, and observation, with a focus on financial literacy training, the formation of savings groups, the selection and training of group committees, entrepreneurship skills training, and the facilitation of low-interest loan access. The results indicate that financial literacy training improved participants’ capacity to manage household finances, while savings groups provided a secure and transparent mechanism for collective saving. Entrepreneurship training encouraged the diversification of productive activities, and strengthened group governance enhanced accountability in group management. Overall, the VSLA-based community service activities proved effective in strengthening economic independence and resilience among rural communities and demonstrate strong potential for replication as a sustainable model of community economic empowerment.